Evidence-based Medicine (Dr. Gordon Guyatt) - Meducator, The; Rayner, Daniel; Kaur, Hargun (The Meducator, 2019)
Dr. Gordon Guyatt is a Distinguished Professor in the Department of Health Research Methods, Evidence, and Impact at McMaster University, and is one of the founders of “evidence-based medicine.” He has played a significant role in over 30 major clinical studies, including large-scale observational and randomized trials and has extensive expertise in study methodology. As the co-founder and co-chair of the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) working group, he has been intimately involved in the development and evolution of the GRADE approach for evaluating research evidence.